2022
DOI: 10.1093/tropej/fmac028
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Trends of Preschool Child Stunting, Wasting and Overweight in the Eastern Mediterranean Region: Still More Effort Needed to Reach Global Targets 2025

Abstract: Background This study was undertaken to analyze and compare Eastern Mediterranean (EM) countries in achievement of WHO nutrition global targets for children growth indicators by 2025. Methods A total of 108 national surveys from 20 countries in EM region were analyzed to estimate the prevalence of stunting and wasting and 93 surveys to estimate the prevalence of overweight/obesity in children. These data were obtained from na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…As shown in Table 1 , all 27 studies included in this review were cross-sectional surveys. Eighteen of these studies were investigated in Egypt [ 30 47 ], and 10 studies explored the problem in Sudan [ 32 , 35 , 38 , 42 , 48 53 ]. In addition, 6 studies assessed prevalence of undernutrition in Morocco [ 32 , 35 , 38 , 39 , 54 , 55 ]; 4 studies assessed prevalence of undernutrition in Libya [ 32 , 38 , 55 , 56 ], 3 studies demonstrated prevalence of undernutrition in Tunisia [ 32 , 35 , 38 ], and 1 study investigated in Algeria [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Table 1 , all 27 studies included in this review were cross-sectional surveys. Eighteen of these studies were investigated in Egypt [ 30 47 ], and 10 studies explored the problem in Sudan [ 32 , 35 , 38 , 42 , 48 53 ]. In addition, 6 studies assessed prevalence of undernutrition in Morocco [ 32 , 35 , 38 , 39 , 54 , 55 ]; 4 studies assessed prevalence of undernutrition in Libya [ 32 , 38 , 55 , 56 ], 3 studies demonstrated prevalence of undernutrition in Tunisia [ 32 , 35 , 38 ], and 1 study investigated in Algeria [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen of these studies were investigated in Egypt [ 30 47 ], and 10 studies explored the problem in Sudan [ 32 , 35 , 38 , 42 , 48 53 ]. In addition, 6 studies assessed prevalence of undernutrition in Morocco [ 32 , 35 , 38 , 39 , 54 , 55 ]; 4 studies assessed prevalence of undernutrition in Libya [ 32 , 38 , 55 , 56 ], 3 studies demonstrated prevalence of undernutrition in Tunisia [ 32 , 35 , 38 ], and 1 study investigated in Algeria [ 35 ]. Six studies were conducted on children aged 6 to 60 months [ 30 , 35 , 40 , 47 , 48 , 51 ], 2 studies investigated children aged 6–24 months [ 41 , 42 ] and only 1 study investigated children from 0–6 months [ 36 ] and the remaining studies focused on children aged 0–60 months [ 31 34 , 37 39 , 43 47 , 49 , 50 , 52 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation